1995
DOI: 10.1017/s0890037x00023125
|View full text |Cite
|
Sign up to set email alerts
|

Broadleaf Weed Control with Clomazone in Pickling Cucumber (Cucumis sativus)

Abstract: Broadleaf weed control ranged from 80% with clomazone at 0.14 kg/ha to 100% with clomazone at 1.12 kg/ha. Broadleaf weed control was higher with clomazone than naptalam or ethalfluralin. The combination of clomazone at 0.14 kg/ha and naptalam at 5 kg/ha or ethalfluralin at 1.25 kg/ha gave more than 90% broadleaf weed control. Clomazone caused chlorosis and bleaching on cucumber leaves but plants rapidly recovered. Cucumber yields were higher in plots treated with clomazone alone at 0.14 to 0.56 kg/ha than with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…), common lambsquarters, common ragweed, and common purslane (Portulaca oleracea L.) (Brown and Masiunas 2002;Jordan et al 1994;Scott et al 1995), but is ineffective on yellow nutsedge (Cyperus esculentus L.), smooth pigweed, or nightshades (Solanum spp.) (Al-Khatib et al 1995;Nurse et al 2006;Trader et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…), common lambsquarters, common ragweed, and common purslane (Portulaca oleracea L.) (Brown and Masiunas 2002;Jordan et al 1994;Scott et al 1995), but is ineffective on yellow nutsedge (Cyperus esculentus L.), smooth pigweed, or nightshades (Solanum spp.) (Al-Khatib et al 1995;Nurse et al 2006;Trader et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In a greenhouse evaluation of selected accessions, the differences in tolerance were not as great as in the field screening experiment. Al-Khatib et al (1995) demonstrated differences in clomazone tolerance among five cucumber cultivars in greenhouse and field experiments. The greatest differences in tolerance were observed with injury ratings taken at 4 weeks after planting in the field and with leaf area and plant dry weights in the greenhouse.…”
mentioning
confidence: 95%
“…Studies have been conducted on reduced doses and spray volumes (e.g., Schumacher and Hatterman-Valenti 2007), but not at the microscale. Dose-response relationships have been used most often for herbicide efficacy (e.g., Al-Khatib et al 1995) and more recently for detecting herbicide-resistant weeds (e.g., Riar et al 2011) and other less common weed control tools, such as flaming (Sivesind et al 2009), clove oil (Boyd and Brennan 2006), and mustard seed meal (Boydston et al 2011). More research is needed to evaluate the response of individual weed species to micro-rates and the efficacy of the equipment used for making targeted applications.…”
Section: Introductionmentioning
confidence: 99%